Direct Impedimetric Detection and Isolation of Bacillus Cereus using Modified Platinum Electrode - Roy, Aashis S.; Ramamurthy, Praveen C. (Journal of Research Updates in Polymer Science, 2017)
This work proposes a technique for isolation of bacteria using magnetic nanoparticles. The magnetic nanoparticles that are prepared by a sol-gel method using citric acid and nano-ferrites are characterized for structural and morphology by X-ray diffraction (XRD) and Transmission electron microscope (TEM), respectively. The prepared nano-ferrites coated with poly vinyl alcohol (PVA) over platinum electrode are used for detection of Bacillus Cereus. The isolated bacterial cells from colloidal solution are treated with zinc ferrite for 12 h, and it is observed that the cells are coagulated with the nanoparticle when allowed to settle down. This is further filtered by different size of filter paper to get less than 0.1% of cells in water. Various electrochemical parameters like cyclovoltammetry (CV), sweep step function, Tafel plot, AC impedance are studied employing the modified platinum electrode. It is observed through CV graph that the peaks are formed at -0.25 V due to the oxidation of bacterial cells, which is further supported by sweep step function graph. Therefore, this is one of the economically efficient techniques to detect and isolate the Bacillus cereus from a colloidal solution.